2019
DOI: 10.1111/emre.12373
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Acquisition for Innovation: Networks of Top Managers in the European Fashion Industry

Abstract: Past research revealed that social networks play a decisive role for the receipt of new knowledge by engineers and middle‐level managers and, thus, essentially contribute to innovation. However, the question of by which network ties top managers – that is, the key organizational decision‐makers – acquire which kind of innovation‐related knowledge resources has not yet been explored systematically. Our paper addresses this research gap by empirically analyzing knowledge ties of top executives in the European fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 74 publications
0
9
0
1
Order By: Relevance
“…Our finding extends Flatten et al ( 2011 ) and Ferreira and Franco's ( 2017 ) results on the role of strategic alliances in European SME performance across a wider range of countries. These are further lessons for SME managers: SMEs operating across our different country groups need to recognize the importance of the intra‐firm governance function's fit and interaction with inter‐organizational networks in the process of knowledge acquisition and innovation, also demonstrated in this journal (Fliaster & Sperber, 2020 ). We show that these considerations are relevant to SMEs and not only to top managers in larger companies.…”
Section: Discussion Conclusion and Limitationsmentioning
confidence: 71%
“…Our finding extends Flatten et al ( 2011 ) and Ferreira and Franco's ( 2017 ) results on the role of strategic alliances in European SME performance across a wider range of countries. These are further lessons for SME managers: SMEs operating across our different country groups need to recognize the importance of the intra‐firm governance function's fit and interaction with inter‐organizational networks in the process of knowledge acquisition and innovation, also demonstrated in this journal (Fliaster & Sperber, 2020 ). We show that these considerations are relevant to SMEs and not only to top managers in larger companies.…”
Section: Discussion Conclusion and Limitationsmentioning
confidence: 71%
“…Blockchain technology has the potential to revolutionize and redesign different sectors worldwide because of organizational learning (Darwish et al , 2018) based on knowledge (Nelson and Kletke, 1990; Fliaster and Sperber, 2019).…”
Section: Managing Increased Complexity and Uncertainty Through Tracea...mentioning
confidence: 99%
“…Building on information processing theory and contingency theory, it can be concluded that intra-organisational collaboration affects innovation projects performance through their effects on the integration and transfer of knowledge within the organisation (De Luca and Atuahene-Gima, 2007;Mu et al, 2009). Intra-organisational collaboration reinforces a double-loop learning process and internal Rosenberg (1988), Xu and Ma (2008) (continued ) (Fliaster and Sperber, 2019;Gupta and Maltz, 2015;Rodr ıguez et al, 2008;Spieth and Joachim, 2017). Internal learning occurs when members of the organisation generate and distribute new knowledge inside the organisation; it depends mainly on the extent of the collaboration among organisation's functional units (Alegre and Chiva, 2008).…”
Section: Collaborative Relationshipmentioning
confidence: 99%